2023
DOI: 10.3390/v15030789
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for CAR-T Cell Immunotherapy in HIV Cure

Abstract: Chimeric antigen receptor (CAR) technology is having a huge impact in the blood malignancy field and is becoming a well-established therapy for many types of leukaemia. In recent decades, efforts have been made to demonstrate that CAR-T cells have potential as a therapy to achieve a sterilizing cure for human immunodeficiency virus (HIV) infection. However, translation of this technology to the HIV scenario has not been easy, as many challenges have appeared along the way that hinder the consolidation of CAR-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Similar to CART therapy in lymphoid malignancies, CART have been created to attack antigens on HIV-1 latently infected cells (Fig. 2) [70]. Early studies added CD4+ T-cell receptors along with its signal transducing intracellular domain to CD8 T cells [71].…”
Section: Cellular Therapy and Hiv-1 Curementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to CART therapy in lymphoid malignancies, CART have been created to attack antigens on HIV-1 latently infected cells (Fig. 2) [70]. Early studies added CD4+ T-cell receptors along with its signal transducing intracellular domain to CD8 T cells [71].…”
Section: Cellular Therapy and Hiv-1 Curementioning
confidence: 99%
“…New approaches include CART therapy that attack several conserved epitopes on the HIV-1 gp160 protein, duoCART, of which clinical trials in PWH without cancer are ongoing and in-vitro studies have shown promise (NCT04648046) [76,77]. Limitations of CART include the product itself can be infected by HIV-1, viral escape (HIV-1 high mutation potential can alter the antigen target), and latently infected cells not accessible to the CART [70]. For a complete review of CART and HIV-1 cure see Campos-Gonzales et al .…”
Section: Cellular Therapy and Hiv-1 Curementioning
confidence: 99%
“…Several obstacles have been encountered in the design of CAR-T therapy, including their infection by HIV-1, viral escape, and a need to broadly target the viral reservoir. These hurdles must be overcome for CAR-T therapy to be effective, as well as combining this therapy with an effective "shock" approach [284].…”
Section: Kill Agentsmentioning
confidence: 99%
“…The unique feature of this targeted therapy is that it multiplies and engrafts to the extent necessary for a sustained therapeutic effect thereby boosting the immunogenic memory and monitoring of viral growth. Unlike other therapeutic objectives, this method is predicted to be most advantageous in terms of completely eliminating cells infected with HIV and preventing viral resurge 5 .…”
mentioning
confidence: 99%
“…This is where the distinctiveness of CAR-T cells is seen. As the CAR recognises antigens directly without the MHC-I limitation, these cells are capable of circumventing the viral escape mechanism with a prolonged duration of action making it a reliable therapeutic approach in the complete elimination of viral load 5 , 6 .…”
mentioning
confidence: 99%